Relaksasi Beban Kerja Guru PAI melalui Upaya Bimbingan Akhlak Siswa pada Masa Covid-19 - Ossi Marga Ramadhan; Hasbiyallah Hasbiyallah; Supiana Supiana (DAYAH: Journal of Islamic Education, 2021)
This study aims to examine the efforts of Islamic Religious Education teachers in guiding the morals of students during the Covid-19 Pandemic, which is done as their responsibility in completing the aspects of guidance on teacher workloads, as well as examining supporting and inhibiting factors and solutions offered to optimize efforts. moral guidance during the pandemic. This research is qualitative descriptive by collecting data through observation, documentation and interviews. Interviews were conducted with 3 (three) PAI teachers at SMAN 1 Jatiluhur. The results show that 1) PAI teachers' moral guidance planning has a focus on cultivating moral values in Allah, oneself, family and the environment; 2) moral guidance is carried out formally and informally using the methods of advice, habituation, ibrah and exemplary. PAI teachers collaborate with homeroom teachers and parents in fostering student attitudes when carrying out online learning, at home and on social media, as well as how students carry out fardhu prayers, sunnah prayers and habituation of reading al-Qur'an. 3) assessment and evaluation are mostly carried out through the google form, google classroom, zoom meeting, whatsapp and youtube platform. PAI teachers develop more interactive PAI teaching materials and assign tasks based on the principle of honesty; 4) The supporting factors for the implementation of moral guidance consist of Islamic Education teachers, homeroom teachers, parents and students; 5) The obstacles faced are limited mastery of IT, limited devices and signals as well as student backgrounds; 6) The solution offered is to consider the selection of the appropriate method of moral guidance and in accordance with the characteristics of students, increased mastery of information and technology and the provision of supporting facilities to assist the process of moral guidance for students during the Covid-19 pandemic.